Elevated antioxidant defence in the brain of deep-diving pinnipeds - Martens, Gerrit A.; Folkow, Lars P.; Burmester, Thorsten; Geßner, Cornelia (Frontiers in Physiology, 2022)
While foraging, marine mammals undertake repetitive diving bouts. When the animal surfaces, reperfusion makes oxygen readily available for the electron transport chain, which leads to increased production of reactive oxygen species and risk of oxidative damage. In blood and several tissues, such as heart, lung, muscle and kidney, marine mammals generally exhibit an elevated antioxidant defence. However, the brain, whose functional integrity is critical to survival, has received little attention. We previously observed an enhanced expression of several antioxidant genes in cortical neurons of hooded seals (Cystophora cristata). Here, we studied antioxidant gene expression and enzymatic activity in the visual cortex, cerebellum and hippocampus of harp seals (Pagophilus groenlandicus) and hooded seals. Moreover, we tested several genes for positive selection. We found that antioxidants in the first line of defence, such as superoxide dismutase (SOD), glutathione peroxidase (GPX) and glutathione (GSH) were constitutively enhanced in the seal brain compared to mice (Mus musculus), whereas the glutaredoxin and thioredoxin systems were not. Possibly, the activity of the latter systems is stress-induced rather than constitutively elevated. Further, some, but not all members, of the glutathione-s-transferase (GST) family appear more highly expressed. We found no signatures of positive selection, indicating that sequence and function of the studied antioxidants are conserved in pinnipeds.